First description of interdigital hyperplasia associated with contagious ovine digital dermatitis in two sheep - Alsaaod, Maher; Schmid, Robin Michael; Zwahlen, Nathalie; Soto, Sara; Wildi, Nicole; Seuberlich, Torsten; Steiner, Adrian (Frontiers in Veterinary Science, 2023)
Interdigital hyperplasia (IH) is a fold of fibrous tissue protruding into the interdigital space that rarely occurs in sheep. Interdigital hyperplasia secondary infected with bovine digital dermatitis (BDD) treponemes has been reported in cattle in the course of the increasing spread of classical BDD lesions. In this report, we describe proliferative/ulcerative interdigital lesions associated with contagious ovine digital dermatitis (CODD) treponemes and clinically scored as (IH+CODD), occurring in both hind limbs of a ram and the left hindlimb of a ewe. Both cases exhibited epidermal hyperplasia, parakeratosis and focal-extensive areas of epidermal necrosis with numerous infiltrating neutrophils. Treponema PCR and fluorescence in situ hybridization (FISH) were positive for Treponema phylotype 1 (PT1). In addition, Dichelobacter (D.) nodosus and Porphyromonas (P.) levii were detected in the biopsy by PCR. In three slaughter sheep, without claw lesions, which were kept together with both affected sheep, Treponema spp. were detected neither with PCR nor FISH; the PCRs for D. nodosus and P. levii were also negative. Complete clinical healing occurred in the ewe within 6 weeks after three local applications of a chlortetracycline spray in 2 weeks intervals. This report is the first description of IH+CODD in sheep as demonstrated by a combination of histopathological and molecular analyses.